RHETORICAL ODYSSEY AND TRAJECTORIES: A PERSONAL REFLECTION - Yazid Basthomi (TEFLIN Journal: A publication on the teaching and learning of English, 2006)
The present paper outlines a self introspective undertaking germane to the issue of rhetorical awareness. This issue is imbricated in the realm of academic writing in English (particularly, English as a foreign language). As a self retrospective endeavor, the paper starts with some personal account undergirding the writing of the present paper. Some self delineation teasing out the context for the rhetorical awareness will also be presented. Some attempts to read the main issue raised in the paper against the backdrop of the wider context (within the gamut of ELT) will conclude the paper.